The Effect of the Capital Adequacy Ratio and Non-Performing Loans on Profitability, With Good Corporate Governance as a Moderator: A Study of Commercial Banks Listed on the Indonesia Stock Exchange, 2020-2024 - Christiani, Evi; Sunarto, Sunarto (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR) and Non-Performing Loan (NPL) on bank profitability with Good Corporate Governance (GCG) as a moderating variable. A quantitative approach was employed using secondary data from annual financial reports of commercial banks listed on the Indonesia Stock Exchange for the 2020–2024 period. The sample consisted of 14 banks selected through purposive sampling, yielding 70 observations. Data analysis was conducted using Moderated Regression Analysis (MRA) with SPSS version 25. The results show that CAR has a significant negative effect on profitability, indicating that high capital adequacy does not necessarily increase profitability without effective capital management, consistent with Signalling Theory. NPL does not have a significant effect on profitability, implying that banks have implemented adequate credit risk management, consistent with Stakeholder Theory. GCG strengthens the effect of CAR on profitability, indicating that good governance improves capital management effectiveness, supporting Agency Theory. However, GCG is unable to moderate the effect of NPL on profitability, suggesting that credit risk management is more influenced by credit analysis quality and macroeconomic conditions than by governance mechanisms. These findings provide empirical evidence on GCG's role in strengthening the relationship between capital adequacy and bank profitability, offering practical implications for banking management in optimizing capital management and implementing corporate governance to improve financial performance. For future research, it is recommended to expand the research period, add macroeconomic control variables, and use more comprehensive GCG proxies.